Analisa Faktor Yang Mempengaruhi Nyeri Haid (Dismenorhea) Pada Mahasiswa Akademi Kebidanan Prima Husada Bogor - Rindasari Munir; Fitria Lestari; Lela Zakiah; Meti Kusmiati; Anggun Anggun; Dhea A; Diva F; Mutia A; Puput Puput (Pusat Riset dan Inovasi Nasional, 2024)
According to the World Health Organization (WHO), the incidence of dysmenorrhea reaches 90%. The prevalence is generally higher in young women in the 17 to 24 year age group, which is estimated at 60-90%. More than 50% of menstruating women in the world report suffering from primary dysmenorrhea. This research was conducted to analyze factors that influence menstrual pain (dysmenorrhea) in students at the Prima Husada Bogor Midwifery Academy. This study used a cross sectional design on 62 samples with a simple random sampling technique. The analysis used is univariate and bivariate with chi square. The research results showed that the age of menarche factor had no influence on menstrual pain in students at the Prima Husada Midwifery Academy with a p value of 0.426 and an Odds Ratio (OR) of 0.659. From the results of the research conducted, it is clear that health education related to dysmenorrhea is very necessary for young women in general and students at the Prima Husada Midwifery Academy in particular by providing counseling related to reproductive health. Teenagers should expand their knowledge about dysmenorrhea so that they know what to do to reduce pain. during menstruation.